Interaction effect of cassava starch × buriti oil on the physical properties of edible films. Issue 6 (28th November 2022) - de Souza, Mariele Nascimento; Piedade, Ana Beatriz Silva; Santos, Thaynara Pegoraro; de Britto, Vitória França; Nascimento, Edgar; de Faria, Jorge Luiz Brito; de Faria, Rozilaine Aparecida Pelegrine Gomes
Abstract: This work aimed to develop and characterize edible films made with cassava starch and buriti oil in a factorial scheme to verify the effect of the interaction between these factors on the physical properties. The experiment was developed in an entirely randomized design in a 2 × 3 factorial scheme. They were prepared with six different formulations evaluating thickness, water solubility, moisture, water activity, chromaticiy ( C *), total color difference (Δ E *), opacity and light transmittance, tensile strength and elongation at break, thermogravimetric analysis, and differential scanning calorimetry. There were effects of each factor on the film properties as well as interaction effects. It was found that with the increase in the concentration of buriti oil, there was a decrease in water solubility, tensile strength, and elongation at break. Higher concentrations of cassava starch increased the thickness and tensile strength. On the other hand, it decreased the moisture content, water solubility, and elongation at break. Transparency, C *, and Δ E * were influenced by the interaction effect between the factors. On the other hand, films with higher oil content showed greater thermal degradation. We conclude that films made with 6% cassava starch and 1% buriti oil present better mechanical and thermal properties with the possibility of application in the food industry. Abstract : Films made with 6% cassava starch and 1% buriti oil showed better mechanical and thermal properties.